Quantification of Plasmodium ex vivo drug susceptibility by flow cytometry. (December 2015) - Wirjanata, Grennady; Handayuni, Irene; Prayoga, Pak; Apriyanti, Dwi; Chalfein, Ferryanto; Sebayang, Boni; Kho, Steven; Noviyanti, Rintis; Kenangalem, Enny; Campo, Brice; Poespoprodjo, Jeanne; Price, Ric; et al.
Abstract Background The emergence and spread of multidrug-resistantPlasmodium falciparum andPlasmodium vivax highlights the need for objective measures of ex vivo drug susceptibility. Flow cytometry (FC) has potential to provide a robust and rapid quantification of ex vivo parasite growth. Methods Field isolates from Papua, Indonesia, underwent ex vivo drug susceptibility testing against chloroquine, amodiaquine, piperaquine, mefloquine, and artesunate. A single nucleic acid stain (i.e., hydroethidine (HE) forP. falciparum and SYBR Green I (SG) forP. vivax ) was used to quantify infected red blood cells by FC-based signal detection. Data derived by FC were compared to standard quantification by light microscopy (LM). A subset of isolates was used to compare single and double staining techniques. Results In total, 57P. falciparum and 23P. vivax field isolates were collected for ex vivo drug susceptibility testing. Reliable paired data between LM and FC was obtained for 88 % (295/334) of these assays. The median difference of derived IC50 values varied from −5.4 to 6.1 nM, associated with 0.83–1.23 fold change in IC50 values between LM and FC. In 15 assays (5.1 %), the derived difference of IC50 estimates was beyond the 95 % limits of agreement; in eleven assays (3.7 %), this was attributable to low parasite growth (final schizont count < 40 %), and in four assays (1.4 %) due to low initial parasitaemia at the start of assay (<2000 µl−1 ). In a subset of seven samples, LM, single and double staining FC techniques generated similar IC50 values. Conclusions A single staining FC-based assay using a portable cytometer provides a simple, fast and versatile platform for field surveillance of ex vivo drug susceptibility in clinicalP. falciparum andP. vivax isolates.